Facilitating dynamic business collaboration Part II - Lai, Louise (2009)
In today’s dynamic environment, Business-to-Business collaboration is very important to stay competitive. Aberdeen’s 2006 survey reported that 80% of 65 companies stated that emphasis on collaboration has increased over the past three years. The way most companies collaborate is via ‘traditional’ way which is phone and fax but this is not sufficient. There is a progression towards electronically collaborating with trading partners. However, current systems and standards are too rigid and unable to formulate collaborative business processes (cBPs) from high-level strategic business goals to low-level operational tasks. This leads to the motivation of this project which is to realize a platform that is dynamic and able to bridge the gap between high-level goals to low-level tasks and to decompose compound business process tasks into primitive operational tasks based on business goals and planning criteria (e.g. product quantity and price) for direct Web Service (WS) execution.